A career open to the talents—Nurses' doing and focus during the history. (28th October 2020) - Falch, Lisbeth Aaskov
Abstract: Based on a historical and a contemporary fieldwork at a Danish hospital, this article offers a genealogical and philosophical exploration of the development of nurses' doing and focus within a hospital setting from the 1800 s to the present day. This exploration finds that nurses' doing has changed during history, which is reflected in their focus. Thus, nurses' focus has developed from, what the Danish philosopher Uffe Juul Jensen refers to as a situation‐oriented, to a disease‐oriented practice, and while new values are established, the conception of care as a core value in nursing seems to have receded. This article also argues that today's nurses are doing what doctors did in the 19th century. The French philosopher Michel Foucault discusses how things repeat themselves in new ways and new contexts. The nursing profession has become 'a career open to the talents' where nurses with the appropriate skills and talents are able to build a career, within which they provide status, position and legitimacy. The conclusion of the article discusses the significance of this development for patients and the nursing profession.